PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA DADU TERJEMAH DALAM PEMBELAJARAN BAHASA INGGRIS SISWA SD - Qothrotun Nada Roniyah; Endang Sri Maruti (Jurnal Prasasti Ilmu, 2026)
This study used translation dice media to complement the Make a Match cooperative learning models in order to enhance students' English learning outcomes. This study employed a Classroom Action Research (CAR) design conducted in two cycles during the even semester of the 2024/2025 academic year, involving 20 second-grade students of SDN 1 Brondong. Data were collected through learning outcome tests, observation, interviews, and documentation. Learning outcome tests were used to measure the improvement of students’ English learning outcomes in each cycle. The results showed that the use of translation dice media to support to improve students’ English learning outcomes. In the pre-cycle stage, 60% of students were in the fair category, 30% in the good category, and 10% in the very good category. After the implementation of actions in Cycle I, the percentage of students in the fair category decreased to 30%, while the good and very good categories increased to 45% and 25%, respectively. More optimal improvement occurred in Cycle II, in which the fair category decreased to 15%, while the good and very good categories increased to 50% and 35%, respectively. These results indicate that this learning model is effective in improving the activities and English learning outcomes of elementary school students.